Information in the aspect of security threats and challenges - Dukiewicz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In the article, the author describes the driving force behind deliberate informational activities. He pays particular attention to the current security situation in the information dimension. Existing systems in the area of security management should be resistant to disinformation and informational operations. There is no room for the freedom of interpretation of the information acquired since every decision results in the actions of people, therefore it requires accuracy and caution. This issue takes on a special dimension when it concerns the state, because this environment contains specific features such as a changing environment, time scarcity and often verified information. Only efficient management of information processes can have a positive impact on the development and elimination of state threats. Actions involving psychological or informational influence may also be carried out by other entities, state-owned, non-state and private, including those located on their own territory. First and foremost, our security depends on ourselves and by taking it into special consideration we also increase the state’s resilience to internal and external threats.
Keywords: przetwarzanie informacji; dezinformacja; system bezpieczeństwa narodowego; bezpieczeństwo narodowe; informacja